2020
DOI: 10.1515/med-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Bowel perforation after ventriculoperitoneal-shunt placement: case report and review of the literature

Abstract: AbstractBowel perforation by a peritoneal catheter (BPPC) is a serious complication after ventriculoperitoneal shunting, with high mortality and morbidity rates. This patient presented with scalp ulceration over the shunt valve at the retromastoid region 26 years after shunt placement. During revision, the catheter distal to the valve was divided in the clavicular region. As there was no cerebrospinal fluid drainage, we decided to remove the ventricular catheter and valve. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Since the infant in that mentioned case had no prior history of any infection in the peritoneal cavity, the first operation of shunt insertion likely has resulted in these adhesions. It has also been suggested that children with congenital conditions such as myelomeningocele and congenital hydrocephalus could be more prone to developing perforation of the bowel due to friable bowel wall possibly caused by the deficient innervation [9][10][11][12][13]. Also, it has been demonstrated that catheters may cause allergies to people with silicone allergies and cause perforation with intestinal irritation and adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the infant in that mentioned case had no prior history of any infection in the peritoneal cavity, the first operation of shunt insertion likely has resulted in these adhesions. It has also been suggested that children with congenital conditions such as myelomeningocele and congenital hydrocephalus could be more prone to developing perforation of the bowel due to friable bowel wall possibly caused by the deficient innervation [9][10][11][12][13]. Also, it has been demonstrated that catheters may cause allergies to people with silicone allergies and cause perforation with intestinal irritation and adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…However, protrusion of the tip of the distal catheter from the anal canal is the most frequent presentation of symptomatic bowel perforation. About 15% to 25% or less of documented cases diagnosed with intestinal perforation also had signs of peritonitis, while 43% to 48% either developed ventriculitis or meningitis [9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations